Body, Senses and Reality in the Italian Theatre of the new Millennium (Itinera, 2020)
The article proposes a study of the Italian theater in the new millennium through the revaluation of the body, of the senses and of the reality. If the main thrust is the presence of the body, the first part studies particularly the definition and the analysis of a language-body, what it is recovered in La madre (2010) of Mimmo Borrelli, methodologically privileging a textual analysis. The second part studies the theatrical relationships, analyzing a particular typology of sensory dramaturgy in the Teatro del Lemming. Beginning from these analyses and from a rapids review of other experiences, the article concludes on the attempt to define what "reality." means today for the theater and to theatre.